KONTRIBUSI KEPEMIMPINAN KEPALA MADRASAH DAN KINERJA GURU TERHADAP HASIL BELAJAR SISWA DI MAN SUMPUR BATIPUH SELATAN KABUPATEN TANAH DATAR - Irawati Fauziah (IAIN Batusangkar, 2016)
Contribution Leadershipof Headmaster and Teacher Performance Toward Students’ Achievement MAN Sumpur Batipuh Selatan Tanah Datar. This study aims toreveal how much the contribution of leadership headmaster and teacher performance to student learning outcomes in Madrasah Aliyah Negeri (MAN/Islamic Senior High School) Sumpur Batipuh Selatan. The hypothesis ofthis study were: (1) Leadership Principals contribute significantly to the performance of the teacher in Madrasah Aliyah Negeri (MAN/Islamic Senior High School) Sumpur Batipuh Selatan Tanah Datar, (2) teacher performance contributes significantly to student learning outcomes in Madrasah Aliyah Negeri (MAN/Senior Islamic High School) Sumpur Tanah Datar, (3) Leadership Principal sand teacher performance are equally contribute significantly to students' learning outcomes in the country Madrasah Aliyah Negeri (MAN/Islamic Senior High School) Sumpur Batipuh Selatan Tanah Datar.The results showedthat: (1) The leadership of headmaster is significantly by 38,1% (Thirty eight poin one percent) of the student learning outcomes in Madrasah Aliyah Negeri (MAN/Islamic Senior High School) Sumpur Batipuh Selatan, (2) the performance of teachers contribute 64,8% (Sixty four poin eight percent) of the student learning outcomes in Madrasah Aliyah Negeri (MAN/Islamic Senior High School) Sumpur BatipuhSelatan, (3) leadership of headmaster and teacher performance together contribute significantly by 58,8% (Fifty eight poin eight percent) of the student learning outcomes in the country Madrasah Aliyah Negeri (MAN/Islamic SeniorHigh School) Sumpur Batipuh Selatan Tanah Datar.The leadership of headmaster and teacher performance are two important factors that cancontribute toward students’ learning outcomes in the Madrasah Aliyah Negeri (MAN/Islamic Senior High School) Sumpur Batipuh Selatan Tanah Datar.Kata Kunci: Kepemimpinan kepala madasah, kinerja guru, hasil belajar siswa